Investigating Plastic Degradation and Spatio-Temporal Microplastic Accumulation in Sediments of the Thames Estuary (UK), its Tributaries, and its Salt Marshes - Trusler, Megan M. (2025)
Context Plastics are diverse, widespread materials used across a range of sectors from packaging to construction. However, their durability allows them to be preserved in the environment and slowly weather into increasingly small particles. Microplastics are any plastic particle less than 5 mm in size, and they have been found to accumulate in environments across the globe. River networks are known to be plastic transport corridors, and coastal estuaries in particular are thought to contain high a high abundance of microplastics, although understanding of microplastic behaviour and accumulation trends remains limited.